The Ambiguity of The President's Position As Head of State And Head of Government - Asri Muhammad Saleh, Moza Dela Fudika,Tamim Ripinra Putra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the ambiguity surrounding the position of the President of Indonesia as both Head of State and Head of Government within the prevailing constitutional system. Although Indonesia has adopted a presidential system based on the 1945 Constitution, political and constitutional realities reveal an overlap between these two roles. Since Indonesia's independence, the country's constitutional system has undergone significant changes, influenced by the historical legacy of the parliamentary system and constitutional amendments aimed at reinforcing the presidential system. However, ambiguity persists because several provisions in the 1945 Constitution still leave room for different interpretations regarding the President's position and authority. This research identifies various factors contributing to this ambiguity, including the impact of patronage politics, unclear relationships between the executive and legislative branches, and the President's political dependence on parliamentary coalitions. Furthermore, the study highlights the need for constitutional reform, which includes clarifying ambiguous provisions, improving the party system, and strengthening the checks and balances mechanism between state institutions. These reforms are expected to clarify the President's position, enhance government effectiveness, and ensure the creation of a more stable, accountable, and democratic administration. This study provides valuable insights into the dynamics of Indonesia's constitutional system and offers solutions for improving the existing governance framework